Terrorism in America - Valeri, Robin Maria; Borgeson, Kevin (Routledge, 2018)
Introduction / Robin Maria Valeri and Kevin Borgeson -- Roots of terrorism -- Theories of terrorism / Thomas R. O'Connor -- Right wing terrorism / Kevin Borgeson -- Left wing terrorism / Michael Loadenthal -- Terrorist beliefs and ideologies -- Christian identity / Kevin Borgeson -- Islamist terror / Christopher J. Wright -- Sovereign citizens / Robin Maria Valeri -- Recruitment and radicalized -- From declaration to deeds / Robin Maria Valeri -- Lone wolf / Joel A. Capellan -- Prison recruitment / Mark Hamm -- Effects of terrorism -- Fear of terrorism / Thomas Monahan and Robin Maria Valeri -- Conclusion / Robin Maria Valeri -- Index